The Role of Dietary Nutraceuticals in Modulating Gut Microbiota and Gene Expression - Drisya Mk; E. Aswathi; Merlin A John (Asian Journal of Pharmaceutical Research and Development, 2025)
Nutraceuticals, originating from phytochemicals and bioactive food components, present an emerging field with promise for health promotion and disease prevention. They serve as a bridge between nutrition and pharmaceuticals for therapeutic benefits, which can include enhance mentsto metabolic function, immune modulation, and chronic disease prevention. The components of nutraceuticals, including, but not limited to, dietary fibres, probiotics, prebiotics, polyphenols, and polyunsaturated fatty acids, not only positively impact health throughout the body, but they also have active, or passive effects on gut microbiota (a unique microbial ecosystem where key aspects of human physiology operate).The gut microbiome is critical for digestion, immunity, neuro regulation, and modulation of disease processes, and can be altered through dietary means. Nutraceuticals have potential therapeutic value in obesity, cardiovascular disease, cancer, inflammatory bowel disease, and neuro degeneration, in part by influencing gut microbiota composition and/or function. An evolving array of omics technologies and machine learning is advancing knowledge on personal nutrition and diet- microbiome interactions. Barriers still exist, for example, the selection of a regulatory body and the standardization of products recognized as nutraceuticals, inter-individual differences and variability in response, and the need to develop systems and metrics to ensure clinical validity. In summary, the fields of nutrigenomics, artificial intelligence, and personalized medicine are advancing the future of functional foods and health-driven dietary shifts.